2012
DOI: 10.1089/cbr.2012.1239
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Intravenous Interleukin-2 with Famotidine Has Activity in Metastatic Melanoma

Abstract: 13 males/8 females, median age, 51 (range: 26-79), and median Eastern Cooperative Oncology Group performance status, 1; common metastatic sites: lymph nodes (16), lungs (14), subcutaneous (8), liver (7), and bone (7). Prior systemic therapy: chemotherapy (7); IL-2 (7); and interferon (5). Most common toxicities were myalgia/arthralgia, rigors, nausea/emesis, and mild elevation of liver function tests. No patients required hospitalization for toxicity of therapy. One patient (5%) has had a complete response (on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Consequently, it is not surprising that IL2 is only successful therapeutically in a minority of patients, ie, some 7% or so. Moreover, some investigators have observed effective clinical responses using intermittent short bolus IL2 dosing, rather than longer IL2 infusions 2,17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is not surprising that IL2 is only successful therapeutically in a minority of patients, ie, some 7% or so. Moreover, some investigators have observed effective clinical responses using intermittent short bolus IL2 dosing, rather than longer IL2 infusions 2,17…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some investigators have observed effective clinical responses using intermittent short bolus IL2 dosing, rather than longer IL2 infusions. 2 , 17 …”
Section: Resultsmentioning
confidence: 99%
“…For example, high doses of IL-2 can be effective but are associated with greater toxicity. However, new data suggest that the addition of famotidine to IL-2 may decrease its toxicity as it enhances lymphokine-activated killer cell activity, whilst maintaining its activity against melanoma [ 58 ]. The CTL response is another example of the beneficial effects brought by the addition of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Regimens including carmustine, cisplatin, dacarbazine, tamoxifen or vinblastine, with or without IL-2 or IL-2 associated with IFN-α achieved a response rate ranging from 23 to 32.5%, with an OS rate of between 4.6 and 11.3 months [ 20 , 54 57 ]. Quan et al recently reported that famotidine may decrease IL-2 toxicity as it enhances lymphokine-activated killer cell activity, whilst maintaining activity against melanoma [ 58 ].…”
Section: Immunomodulatory Agentsmentioning
confidence: 99%
“…Notably, 10-year-survival rates have been high in patients who consisted these 7% (Atkins et al, 1999;Fisher et al, 2000;Klapper et al, 2008;Grivas and Redman, 2011;Prieto et al, 2012). Interestingly, certain studies have reported effective clinical responses using intermittent short bolus IL-2 dosing rather than longer IL-2 infusions (Grivas and Redman, 2011;Quan et al, 2012). In certain situations, either IL-2 and/or IL-2R can be released or expressed by cancer cells themselves Alileche et al, 1993;Coventry et al, 1996;Barbour and Coventry, 2003;Rangel-Corona et al, 2010).…”
Section: Interleukin-2 and Cancermentioning
confidence: 99%